New Radiocarbon Dates Show Early Neolithic Date of Flint-Mining and Stone Quarrying in Britain. Issue 1 (7th February 2020) - Edinborough, Kevan; Shennan, Stephen; Teather, Anne; Baczkowski, Jon; Bevan, Andrew; Bradley, Richard; Cook, Gordon; Kerig, Tim; Parker Pearson, Mike; Pope, Alexander; Schauer, Peter
ABSTRACT: New radiocarbon ( 14 C) dates suggest a simultaneous appearance of two technologically and geographically distinct axe production practices in Neolithic Britain; igneous open-air quarries in Great Langdale, Cumbria, and from flint mines in southern England at 4000–3700 cal BC. In light of the recent evidence that farming was introduced at this time by large-scale immigration from northwest Europe, and that expansion within Britain was extremely rapid, we argue that this synchronicity supports this speed of colonization and reflects a knowledge of complex extraction processes and associated exchange networks already possessed by the immigrant groups; long-range connections developed as colonization rapidly expanded. Although we can model the start of these new extraction activities, it remains difficult to estimate how long significant production activity lasted at these key sites given the nature of the record from which samples could be obtained.